A New Luminescent Zn(II) Compound With 2D→3D Interdigitated Framework. Issue 1 (2nd January 2016) - Zhang, Zhihua
Abstract : A new Zn(II) compound, namely [Zn(pam)(bib)]n (1 H2 pam = pamoic acid, bib = 1, 4-bis(imidazolyl)butane), has been synthesized by the reactions of Zn(II) ions with H2 pam and bib ligands under solvothermal conditions. Single-crystal X-ray analysis reveals that compound1 features a 2D→3D interdigitated supramolecular framework. In addition, the luminescent properties of1 were also investigated at room temperature.